Investigation of blister formed on coated mild steel using scanning Kelvin Probe - Sahir, Zalilah Sharer (Penerbit UTM Press, 2011)
The degradation of a coated metal in term of the area underneath a blister has been studied after being immersed in 3% sodium chlorida and 3% ammonium chloride solution. Scanning Kelvin probe (SKP) was used to map electrochemical potentials, identifying anodic and cathodic regions underneath a blister and the surrounding coating. For blisters formed on coated panel immersed in sodium chlorida solution, SKP potential map reveals that the blister has formed at a cathode due to alkali but anodes form nearby (not remote). Meanwhile SKP potential map for blister formed on coated panel in 3% ammonium chloride reveals the presence of cathodic regions within the anodic areas.